Maternal siRNA silencing of placental SAA2 mitigates preterm birth following intrauterine inflammation - Liu, Yang; Liu, Jin; Liu, Anguo; Yin, Hillary; Burd, Irina; Lei, Jun (Frontiers in Immunology, 2022)
The placental inflammatory processes induced maternally result in preterm birth (PTB). Serum amyloid A (SAA) is a well-known biomarker of inflammation. The objective of this study was to investigate whether murine placental SAA isoforms (SAA1–4) participate in the mechanism of spontaneous PTB and whether maternal regulation of SAA production may serve as a therapeutic approach. During the gestation, all isoforms of SAA were detectable except SAA2. The mouse model of intrauterine inflammation was established using LPS infusion to the uterus. Following intrauterine inflammation, placental SAA2 increased significantly. Inhibition of Saa2, using siSaa2, markedly decreased PTB. The increased placental expression of pro-inflammatory cytokines Il1β, Il6, and Tnfα were downregulated by siSaa2 treatment. Maternal inhibition of Saa2 did not change the expression of Saa1–4 in the fetal brain. Explant inflammatory culture of placentas with siSaa2 showed similar results to our in vivo experiments. This study demonstrates the highly expressed placental SAA2 as a novel therapeutic target, and maternal administration of siRNA as a promising approach to alleviate PTB.